2020
DOI: 10.1007/s11612-020-00506-0
|View full text |Cite
|
Sign up to set email alerts
|

Anwendungsszenarien und Technologiebewertung von digitalen Werkerassistenzsystemen in der Produktion – Ergebnisse einer Interview-Studie mit Experten aus der Wissenschaft, der Politik und der betrieblichen Praxis

Abstract: Zusammenfassung Die Einführung neuer digitaler Technologien wie digitale Werkerassistenzsysteme (z. B. Datenbrillen und Tablets) im Produktionsbereich führen zu Veränderungen der Arbeitswelt. Bestehende Modelle der Arbeitsgestaltung betrachten Technologien als Antezedenzien für die Arbeitsgestaltung. Die Theorie der sozialen Gestaltung von Technologien nimmt an, dass unterschiedliche Akteure Einfluss auf die Gestaltung und Verbreitung von Technologien im betrieblichen Kontext nehmen. Bisher ist kaum bekannt, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 50 publications
2
19
5
2
Order By: Relevance
“…Die Haupteinsatzgebiete der Systeme sind dabei Kleinserien in der Fertigung und Montage [6,7]. Die wichtigsten Funktionen der verwendeten Assistenzsysteme sind die Unterstützung bei der Arbeitsaufgabe, die Qualitätssicherung sowie das Prozessmanagement [8]. Realisiert wird die Assistenz in der Montage zumeist durch Visualisierung (67 %) [6].…”
Section: Stand Der Technikunclassified
See 1 more Smart Citation
“…Die Haupteinsatzgebiete der Systeme sind dabei Kleinserien in der Fertigung und Montage [6,7]. Die wichtigsten Funktionen der verwendeten Assistenzsysteme sind die Unterstützung bei der Arbeitsaufgabe, die Qualitätssicherung sowie das Prozessmanagement [8]. Realisiert wird die Assistenz in der Montage zumeist durch Visualisierung (67 %) [6].…”
Section: Stand Der Technikunclassified
“…Trotz des vorhandenen Potenzials erfolgt die Anwendung dieser Systeme im industriellen Umfeld langsam [8]. Bisherige hemmende Faktoren für den Einsatz sind vor allem die hohen Kosten, fehlende technische Voraussetzungen sowie Unklarheit über die sachgerechte Anwendung [6].…”
Section: Stand Der Technikunclassified
“…In order to be able to fix faults in such complex systems, employees need specialized knowledge (Fréour et al 2021;Pfeiffer 2018a). In addition, smart technologies can provide relevant information to employees, enabling learning on the job, accomplishing more complex and diverse tasks, or greater participation in problem-solving processes (Blumberg and Kauffeld 2020;Szalavetz 2021). There are also risks for knowledge characteristics at work (Blumberg and Kauffeld 2020), such as simplification of work activities, which might result in a reduction of the variety of requirements or de-skilling (Kunst 2019;Szalavetz 2021).…”
Section: Work Design and Smart Technologiesmentioning
confidence: 99%
“…Therefore, it is im-K portant to distinguish different applications of smart wearables. Facing this research gap, a recent interview study (Blumberg and Kauffeld 2020) examined smart wearables and mobile smart devices in industrial work and identified nine different categories of their application: communication (application for communication within and outside the team e.g. by voice, text or videos), identification (application for identification or registration at workplaces), management (application for the collection, analysis and evaluation of process data), navigation (application for navigation), occupational safety and health (application for the protection of employees from harmful stresses and hazards), coordination (application to support process and coordinative activities), competence development (application to support learning and teaching processes), quality assurance (application to ensure the quality of products and processes), and work task support (application to help employees in performing their work tasks).…”
Section: Smart Wearables In Industrial Workmentioning
confidence: 99%
See 1 more Smart Citation